Improved connectivity and cognition due to cognitive stimulation in Alzheimer’s disease - Behfar, Qumars; Richter, Nils; Kural, Merve; Clemens, Anne; Behfar, Stefan Kambiz; Folkerts, Ann-Kristin; Fassbender, Ronja; Kalbe, Elke; Fink, Gereon R.; Onur, Oezguer A. (Frontiers in Aging Neuroscience, 2023)
Background: Due to the increasing prevalence of Alzheimer’s disease (AD) and the limited efficacy of pharmacological treatment, the interest in non-pharmacological interventions, e.g., cognitive stimulation therapy (CST), to improve cognitive dysfunction and the quality of life of AD patients are on a steady rise. Objective: Here, we examined the efficacy of a CST program specifically conceptualized for AD dementia patients and the neural mechanisms underlying cognitive or behavioral benefits of CST. Methods: Using neuropsychological tests and MRI-based measurements of functional connectivity, we examined the (neuro-)psychological status and network changes at two time points: pre vs. post-stimulation (8 to 12 weeks) in the intervention group (n=15) who received the CST versus a no-intervention control group (n=15). Results: After CST, we observed significant improvement in the Mini-Mental State Examination (MMSE), the Alzheimer’s Disease Assessment Scale, cognitive subsection (ADAS-cog), and the behavioral and psychological symptoms of dementia (BPSD) scores. These cognitive improvements were associated with an up-regulated functional connectivity between the left posterior hippocampus and the trunk of the left postcentral gyrus. Conclusion: Our data indicate that CST seems to induce short-term global cognition and behavior improvements in mild to moderate AD dementia and enhances resting-state functional connectivity in learning- and memory-associated brain regions. These convergent results prove that even in mild to moderate dementia AD, neuroplasticity can be harnessed to alleviate cognitive impairment with CST.